2018
DOI: 10.15171/jept.2018.01
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low back pain and its related factors among pre-hospital emergency personnel in Iran

Abstract: Objective: Low back pain is one of the most important job injuries among emergency medical personnel. This study was carried out to investigate the prevalence of low back pain as well as its physical, mental and managerial predisposing factors among emergency medical personnel in Iran. Methods: In this analytical cross-sectional study we recruited 298 pre-hospital emergency medical personnel based on census sampling. Data were gathered using Nordic and a research-made questionnaire related to physical, mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
7
0
5
Order By: Relevance
“…Previous studies from China, Japan, and Iran reported a prevalence of lower back issues of 12% to 66% in pre-hospital emergency workers (Imani et al 2018 ; Okada et al 2005 ; Zhang et al 2019 ). This is in the range of the present study, identifying pain at lumbar spine in almost 66% of participating pre-hospital EMS personnel with pain (59%), which corresponds to almost 40% of the full study population.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies from China, Japan, and Iran reported a prevalence of lower back issues of 12% to 66% in pre-hospital emergency workers (Imani et al 2018 ; Okada et al 2005 ; Zhang et al 2019 ). This is in the range of the present study, identifying pain at lumbar spine in almost 66% of participating pre-hospital EMS personnel with pain (59%), which corresponds to almost 40% of the full study population.…”
Section: Discussionmentioning
confidence: 97%
“…People working in pre-hospital emergency medical service (EMS) are an essential group of skilled healthcare professionals, evaluating acute patients and providing first care (Ilper et al 2014 ; Klepacka et al 2018 ). It is also known that people working in pre-hospital EMS are often suffering from back complaints (Imani et al 2018 ; Maguire et al 2005 ; Okada et al 2005 ; Zhang et al 2019 ). A study with Chinese ambulance drivers indicated a 1-year prevalence of lower back pain lasting for at least 3 months of 12.3% (Zhang et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lokalizacja dolegliwości bólowych i ich częstotliwość u badanych W przeprowadzonym badaniu wszyscy ankietowani zadeklarowali występowanie ZBK z różną częstotliwością w ciągu ostatnich 12 miesięcy. Największym problemem u ratowników, zarówno w Polsce, jak i na świecie, są dolegliwości dolnego odcinka kręgosłupa [2,4,6,13,14]. W badaniu własnym występowanie bólów głównie w okolicy lędźwiowo--krzyżowej zadeklarowało aż 65% badanych, odcinku szyjnym -20%, a w piersiowym -15% osób.…”
Section: Dyskusjaunclassified
“…In the present study, intrapersonal challenges were one of the issues that personnel were involved with. The results of different studies have shown that pre-hospital EMS personnel suffer from intervertebral discs, osteoarthritis, back pain and anatomical disorders [31][32][33]. Although the results of these studies were expressed quantitatively, they still indicate the challenge of physical problems among these personnel.…”
Section: Discussionmentioning
confidence: 99%